Relevance of the retrieval and use of information from the user standpoint of the Agronomy and Veterinary Library. Northeastern National University (Corrientes, Argentina) - Felquer, Lucrecia Viviana; López Huertas, María José; Giménez, Laura (Revista General de Información y Documentación, 2015)
In the traditional evaluation of information-retrieval systems, the relevance of a document is determined on a graded scale. At present, relevance is judged from the user’s perspective. In this paper, the relevance is measured on documents that are used for any academic purpose by the users of the Agronomy and Veterinary Library of the Northeastern National University (Corrientes, Argentina). Users are specialized in both fields. We will focus on the relevance analysis of the documents obtained and used for different purposes according to their usefulness, originality, accuracy, clarity, authority, and updatedness. Spearman Coefficient Correlation has been used to determine the relationships between the variables. User types studied in the present paper are graduate and postgraduate students, researchers, academic teachers and external users. This study also shows the importance of each criterion to the general relevance of document from the user standpoint. It is believed that an adequate remote connection would permit a better, fluid access to online information resources and will reinforce the online information services by the library. It is also noted that users need a hardly instruction in the use of the available printed and online resources.